2022
DOI: 10.3390/ijerph19031361
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes, Adaptation, and Supports among Indonesian Female Sex Workers Facing Dual Risk of COVID-19 and HIV in a Pandemic

Abstract: The objective of this study is to explore the impacts of COVID-19 and changes taking place among the Indonesian female sex worker (FSW) community during the COVID-19 pandemic and the predictors of these changes. We conducted a cross-sectional online survey and selected the participants using a purposive snowball sampling technique. Incentives were provided to participants in the form of a 5 USD e-wallet balance. Variables of interest included adaptation to online sex work, adherence to COVID-19 prevention meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…VSW in low- and middle-income Countries (LMICs) remains under-researched, though important studies address this topic as part of the broader literature on sex work in LMICs. 3 , 21 , 28 , 29 Similarly, technology-facilitated IPV research, including a seminal study led by sex workers in the European Union, 8 has concentrated on European and US contexts 30 despite calls to “decolonize[e] privacy studies”. 31 Technology-facilitated IPV is a global problem that requires digital privacy and security solutions adapted to local contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VSW in low- and middle-income Countries (LMICs) remains under-researched, though important studies address this topic as part of the broader literature on sex work in LMICs. 3 , 21 , 28 , 29 Similarly, technology-facilitated IPV research, including a seminal study led by sex workers in the European Union, 8 has concentrated on European and US contexts 30 despite calls to “decolonize[e] privacy studies”. 31 Technology-facilitated IPV is a global problem that requires digital privacy and security solutions adapted to local contexts.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Some sex workers shifted to VSW, although this was not feasible for many, due to barriers like cost and inconsistent internet access. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, the utilisation of medical facilities and benefits raises psychological, contextual, systemic, and biomedical concerns about sexual health and HIV mitigation (Newman and Guta 2020 ). The Covid-19 pandemic has hampered FSWs’ access to socioeconomic support systems and HIV preventive programmes, putting them at risk of both HIV and Covid-19 infections in Indonesia (Wirawan et al 2022 ). The loss of subsistence and inadequate access to health care and social protection aggravated the exploitation of sex workers in India, particularly those living with HIV (Paul et al 2017 ).…”
Section: Disruption Of Hiv Programsmentioning
confidence: 99%
“…It was also observed that continuing sex work even during the pandemic protected FSWs from major income loss, whereas education and younger age anticipated adaptive behavioral changes, such as taking up online sex work. Further, the Covid-19 pandemic has affected FSWs access to socioeconomic assistance programs and HIV prevention services, exposing them to the dual threat of HIV and Covid-19 infections (Wirawan et al 2022 ).…”
Section: Vaccination Drivesmentioning
confidence: 99%